Răspuns :
a+b+c=870
a+b=644
b+c=453
a=870-453=417
b=644-417=227
c=453-227=226
a+b=644
b+c=453
a=870-453=417
b=644-417=227
c=453-227=226
Pai mai intai il afli pe c inlocuid pe a si b
a+b+c= 870
644+c= 870
c= 870-644
c= 226
Dupa il afli pe a inlocuid pe b si c
a+453=870
a=870-453
a= 417
Dupa il afli pe b inlocuind cu ce ai aflat
417+b+226=870
b+643=870
b=870-643
b=227
a+b+c= 870
644+c= 870
c= 870-644
c= 226
Dupa il afli pe a inlocuid pe b si c
a+453=870
a=870-453
a= 417
Dupa il afli pe b inlocuind cu ce ai aflat
417+b+226=870
b+643=870
b=870-643
b=227